Export Packaging Technology for Jasmine - Jawaharlal, M.; Ganga, M.; Thamaraiselvi, S. P.; Karthikeyan, S. (Indian Farming, 2015)
The export packaging technology for jasmine developed in the project has promoted jasmine export considerably. All possible efforts are being made to make the technology reach farther.